Abundance and Community Structure of Reef Fish (Family Acanthurudae) Catches Landed by Fishermen at the Fishermen's Fish Market, Pondokdadap Coastal Fishing Port, Malang Regency, East Java - Sabilatul Mufarrohah; Husain Latuconsina; Hamdani Dwi Prasetyo; Anthon Andrimida (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
The Acanthuridae family is a group of fish that inhabits coral reef ecosystems of medium to large size, generally found in various types of coral reef habitats with diverse live coral cover. This study aims to analyze the abundance, frequency of presence, and community structure of fish from the Acanthuridae family landed by fishermen at the Fishermen's Fish Market in the Pondokdadap Coastal Fishing Port. The study lasted for three months (April - June 2025) with sampling times every two weeks. Data analysis includes relative abundance, frequency of presence, and community structure (Diversity, Evenness, and Dominance indices). The results of the study identified eight fish species from the Acanthuridae family with a total of 79 individuals, Acanthurus xanthopterus with 44 individuals with a relative abundance of 56%, and a frequency of presence of 83% which is categorized as commonly found. Community structure values including the diversity index are categorized as low, the evenness index is unstable, and the dominance index is low. The conservation status of four species (50%) of fish is Least Concern (Acanthurus lineatus, Acanthurus xanthopterus, Naso elegans, and Naso unicornis). While the other 50% of species are categorized as Data Deficient (Naso tuberosus, Naso reticulatus, Ctenochaetus binotatus, Prionurus chrysurus). However, continuous monitoring of the catch level and population status of fish of the Acanthuridae family in the waters of the Sempu Strait directly adjacent to the Pondokdadap Coastal Fishing Port is needed to provide important information in determining the appropriate fisheries management model.